Penetrating Trauma A Practical Guide on Operative Technique and Peri-Operative Management - Velmahos, George C.; Degiannis, Elias; Doll, Dietrich (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Surgery needs skill. Skill needs knowledge. Knowledge of tricks, moves, and tools. This book is about such knowledge. Expert authors have contributed technical pearls, gained by years of experience. The short "how-I-do-it" chapters offer the reader a quick and effective guide that will be invaluable when addressing any penetrating injury.   The book is not intended to serve as a comprehensive volume of pathophysiology and management in trauma; rather the goal is to provide practical solutions on how to treat injuries surgically. It describes the steps that you must take when, in the middle of the night, confronted with devastating bleeding, you will have only one chance to save a life!